AB0692 Association of Anti-SCL70 Antibodies with Coronary Microvascular Dysfunction in Patients with Systemic Sclerosis. (9th June 2015) - Pigatto, E.; Famoso, G.; Zanatta, E.; Favaro, M.; Scanu, A.; Oliviero, F.; Punzi, L.; Tona, F.; Cozzi, F.
Abstract : Background: Functional impairment of coronary microcirculation is thought to be a major pathway in the development of primary cardiac involvement in systemic sclerosis (SSc); however, the underlying mechanism is not fully understood. Moreover, coronary microvascular dysfunction (CMD) predicts major adverse outcomes in several cardiovascular diseases. Specific autoantibodies represent a serologic hallmark which have relevance in the diagnosis and prognosis of SSc. Some biomarkers are involved in the pathogenesis of SSc: endothelin-1 (ET-1, marker of endothelial dysfunction), interleukin-6 and iterleukin-17 (IL-6 and IL-17, markers of immune activation), and transforming growth factor-β (TGF-β, marker of fibroblast stimulation). Objectives: To assess the relationship between coronary flow reserve (CFR), a marker of CMD, and specific autoantibodies: antitopoisomerase I (anti-Scl70) and anticentromere (ACA). Methods: Fifty-four patients (30 F, 24 M, aged 58±12 years) with cutaneous diffuse (n=24) or limited (n=30) SSc, without clinical evidence of heart disease, and 50 healthy controls were enrolled. Activity score (1) was calculated in all patients. Coronary flow velocity in the left anterior descending coronary artery was detected by transthoracic Doppler echocardiography (TDE) at rest and during adenosine infusion. CFR was the ratio of hyperaemic diastolic flow velocity (DFV) to resting DFV. A CFR≤2.5 was considered abnormal and marker of CMD. Antitopoisomerase I (anti-Scl70) antibodies, anticentromere (ACA) antibodies, IL-6, IL17, ET-1 and TGF-β were investigated in all patients. Results: CFR was lower in patients with SSc than in healthy controls (2.3±0.7 vs 3.5±0.4, p<0.0001). The prevalence of CMD was higher in patients than in controls (61% vs 3%, p<0.0001). CFR was related to time from diagnosis (r=-0.318, p=0.01), activity score (r=-0.432, p=0.006), IL-6 (r=-0.321, p=0.04) and ET-1 (r=-0.320, p=0.04). Patients with CMD (CFR≤2.5) showed an higher activity score (2.4±1 vs 1.2±0.8, p=0.008). Scl70 antibodies were more frequent in the diffuse form of SSc (p<0.0001). CFR was lower in patients with anti-Scl70 antibodies compared to patients with ACA antibodies (2.1±0.6 vs 2.6±0.8, p=0.02) (Figure ), but comparable in patients with diffuse and limited form of SSc (2.36±0.6 vs 2.34±0.8, p=0.9). Moreover, CMD was more frequent in patients with anti-Scl70 antibodies compared to patients with ACA antibodies (73% vs 49%, p=0.04), whereas CMD was equally present in diffuse and limited form of SSc (62.5% vs 60%, p=0.8). Conclusions: Our data show that anti-Scl70 antibodies are associated with coronary microvascular dysfunction independently from the cutaneous form of SSc. The evaluation of specific autoantibodies could represent a tool for the prediction of coronary microvascular dysfunction, a severe organ involvement in this disease. References: Valentini G et al. Ann Rheum Dis 2001 Disclosure of Interest: None declared